Redheaded women are more sexually active than other women, but it is probably due to their suitors - Sýkorová, Kateřina; Fiala, Vojtěch; Hlaváčová, Jana; Kaňková, Šárka; Flegr, Jaroslav (Frontiers in psychology, 2022)
Women with red hair color, i.e., 1–9% of female Europeans, tend to be the subject of various stereotypes about their sexually liberated behavior. The aim of the present case–control study was to explore whether a connection between red hair color and sexual behavior really exists using data from 110 women (34% redheaded) and 93 men (22% redheaded). Redheadedness in women, correlated with various traits related to sexual life, namely with higher sexual desire as measured by Revised Sociosexual Orientation Inventory, with higher sexual activity and more sexual partners of the preferred gender over the past year, earlier initiation of sexual life, and higher sexual submissiveness. Structural equation modelling, however, showed that sexual desire of redheaded women mediated neither their higher sexual activity nor their higher number of sexual partners. These results indirectly indicate that the apparently more liberated sexual behavior in redheaded women could be the consequence of potential mates’ frequent attempts to have sex with them. Our results contradicted the three other tested models, specifically the models based on the assumption of different physiology, faster life history strategy, and altered self-perception of redheaded women induced by stereotypes about them. Naturally, the present study cannot say anything about the validity of other potential models that were not subjects of testing.